Metasurface inspired printed dual‑port MIMO antenna system with LP to CP conversion features for millimeter wave n260 band applications - Anitha C; Vivek Singh; Ajay Kumar Dwivedi; Nagesh Kallollu Narayanaswamy (Scientific Reports)
Abstract A cutting-edge antenna system has been developed for new radio (NR) millimeter wave operating from 36.0 to 40.0 GHz frequency range 2 (FR 2) n260 band applications. This innovative system incorporates metasurface-inspired printed dual-port MIMO technology, which includes LP to CP conversion features. The positional orientation of the elements of the MIMO antenna with stacked metasurface provoked the spatial diversity. To convert linearly polarised (LP) waves to circularly polarised (CP) waves, the metasurface layer is suspended above the MIMO antenna. LP to CP polarisation conversion occurs when the conducting strip and rectangular space between strips on the substrate generate π/2 phase-shifted electric field components (Ex and Ey). The proposed stepped impedance-fed antenna elements and metasurface are fabricated on commercially available high-frequency laminates using a double-layer printed circuit board (PCB) fabrication facility. The test findings exhibit a satisfactory level of concurrence with the calculated/measured findings regarding scattering parameters, diversity performance parameters, and realized gain. The result is a highly efficient and versatile antenna system that is ideal for advanced engineering applications.